Implikasi Hukum Pengujian Peraturan Daerah Pasca Amandemen Undang-Undang Dasar 1945 - King Faisal Sulaiman (Perspektif Hukum, 2019)
This study aims to explain in detail why the dualism of local regulations testing after the amendment of the 1945 Constitution Research is also directed to provide a testing system solutions in the future regulation. Legal discourses are still academic debate is when the right of judicial review by the Supreme Court Regulation hostage by Law No. 23 of 2014 on Regional Government. Supremacy of the constitution as part of the main characteristics of the legal state impressed distorted due to the duality of the regulation testing including how the implications of the Constitutional Court Number 137 PUU-XIII / 2015 Jo Court Number 56 / PUU-XIV / 2016 on June 14, 2017 last. Position regulation as executive versus legislative product as much a part of this study in order to find the ideal solution testing legislation in the future.The research method used was a normative legal research (legal research) which is based on the study of literature or secondary data divided form the primary legal materials, secondary law material and tertiary legal materials. Models used approach is the approach of law (statute aproach) and conceptual approach (conceptual aproach). A number of secondary data collected will be analyzed by descriptive qualitative where the process used deductive thinking. To get accuracy of understanding (subtilitas itellegendi) and accuracy translating (subtilitas explicandi) to solve the problem formulation.